The IVDG Regimen is the Possible Treatment of Choice as First Line Therapy For Hodgkin’s Lymphoma in Elderly Patients with Cardiovascular and Pulmonary Comorbidity - KD Kaplanov; TYu Klitochenko3; AL Shipaeva; MN Shirokova; IV Matveeva; NB Lavrishina (Клиническая онкогематология)
Background. Among the newly diagnosed patients with Hodgkin’s lymphoma (HL), the proportion of elderly patients account for 15–35 %. In > 60 age group the choice of antitumor treatment requires an more individualised approach compared to a younger population. The ABVD regimen is acceptable in terms of efficiency and hematological toxicity, but is associated with a high risk of bleomycine-induced pulmonary complications. In ≥ 60 age group the morbitity and mortality of pulmonary complications account for 24 % and 18 %, respectively.